Surgeon interpretation of patient-reported outcome measures in upper extremity osteoarthritis - Rick S. Looman; Koen D. Oude Nijhuis; Sina Ramtin; David Ring; Daniel A. London; Ryan Calfee; Niels Brinkman (PLoS ONE, 2025)
Purpose Measures that quantify levels of pain intensity, incapability, symptoms of distress, and unhelpful thinking were designed as research tools. We studied how surgeons interpret and act on these scores in the care of individual patients. Methods In an online experiment, 67 upper limb specialists from the Science of Variation Group reviewed 10 fictious patient scenarios of trapeziometacarpal, wrist and elbow osteoarthritis (OA) and randomized elements of radiographic severity, levels of discomfort and incapability, deprivation index score (social health), and levels of distress and unhelpful thinking (mental health). Multilevel mixed-effects linear regression identified patient factors associated with surgeon concern, enthusiasm to offer surgery, motivation to discuss mental health and social circumstances, and likelihood to refer for mental/social health care. Results Higher levels of discomfort, incapability, distress, unhelpful thinking, and deprivation were associated with greater surgeon concern, increased motivation to discuss or refer for mental and social health, and greater motivation to refer for mental/social health. Greater likelihood to offer surgery was associated with greater discomfort and incapability, greater radiographic severity, wrist and elbow OA, and greater distress/unhelpful thinking. Conclusions Measures that quantify the subjective aspects of illness draw surgeon attention to mental and social health, and can be used to inform comprehensive, biopsychosocial diagnostic and treatment strategies.